COLD ANTIBODY-MEDIATED AUTOIMMUNE HEMOLYTIC ANEMIA IN A PATIENT WITH OVERLAP SYNDROME OF SYSTEMIC LUPUS ERYTHEMATOSUS WITH SJOGREN’S SYNDROME - BAIRY, INDIRA; BERWAL, ANUPAM; V, CHARANTHEJREDDY; PRABHU, MUKHYAPRANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disorder commonly seen in females characterized by multisystem inflammation with the production of an array of antibodies. Hematological disturbances are common in SLE specifically autoimmune hemolytic anemia (AIHA) which results from the development of autoantibodies directed against antigens on the surface of patient’s own red blood cells. Here, we present a rare case of a 50-year-old female patient presenting with cold antibody-mediated AIHA.